A paixão de Bach e os fundamentos Weberianos para uma sociologia da música - Monica de Paula Bonfim (2006)
The objective is to establish a connection between some principles of sociology of Weber's music and his sound reflection in sacred work "The Passion According to St. Matthew" by Johann Sebastian Bach, identifying some elective affinities between the productions of these two exponents of German culture. For so much, the dissertation begins with a reflection about the general interests of the Webers thought, going to the analysis of the foundations that, for Weber, they allowed a dizzy development for the western music - especially the one of the rationalization of the of the music (social and technical conditions of production, tension among the musical sphere with the spheres religious person and political) and the internal elements (autonomous logic). Starting from the formal and stylistic analysis of some arias of the Passion Second Saint Mattew, the dissertation emphasizes the approach of the works of Weber and Bach, due to his/her constructive character, proteiform and polyphonic.